Kontribusi Nilai-nilai Keimanan dan Kemanusiaan Persaudaraan Cinta Tanah Air Indonesia - Abdullah, Mukhammad (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2017)
The existence of the PCTA-I (Persaudaraan Cinta Tanah Air-Indonesia/Brotherhood for the Love of Indonesia Homeland) plays a pivotal role, especially for underprivileged people regardless of their religion and faith, tribe, and race. This organization has been, therefore, undeniably desirable to help the Indonesian society overcome their social problems. Focusing its discussion on the PCTA-I, this article seeks to answer such questions as how this organization has been initiated; what does it do to help overcome national problems, and what are the obstacles it faces in implementing the programs and how does it overcome such obstacles? A number of leaders and members of the PCTA-I Central Board have been interviewed. The murshid of the Tarekat ?idd?q?yah has been among the main informants of this study. Employing qualitative approach by focusing on interview, questionnaire, and documentation as the sources of data, the study indicates that the PCTA-I has been able to efficiently implement its programs due to solid participation and robust support of its voluntary community. Through its programs, the PCTA-I attempts to build what so-called ?the soul of society? in order to achieve civilized and enlightened future of Indonesia.